Uji Coba Gim Edukasi dalam Meningkatkan Hasil Belajar Bahasa Inggris - Arsyad, Susalti Nur; Runniarsiti, Runniarsiti; Swandi, Ahmad; Fauzan, Arief; Viridi, Sparisoma; Burhan, Burhan; Rahmadhanningsih, Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
ABSTRACT This study aims to test the effectiveness of educational game-based digital learning media in improving grade IV elementary school English learning outcomes. The pre-experimental design and One Group Pretest-Posttest were used in this study with a sample of 20 students in a school in Makassar. Pretests and posttests are given to learners to obtain data on improving learning outcomes, which are then analyzed using t-tests and N-Gain. The results showed that there was a significant difference in test results between pretest and posttest seen from the sig.2-tailed value of 0.000, where this result was smaller than 0.05. In addition, an N-Gain of 0.49 indicates a moderate category and indicates that the trial of educational game-based digital learning media can improve student learning outcomes. Educational games can be used as an effective learning medium in the learning process and need to be developed in a better direction. Keywords: Learning Media, Educational Games, Learning Outcomes.